Oral Presentations Abstracts: DOES INSTITUTIONALISING REASONABLE ACCOMMODATION INCREASE CONSCIENTIOUS OBJECTIONS OF MEDICAL PROFESSIONALS? - ISHIKAWA, Ryoko (Studia Universitatis Babeş-Bolyai Bioethica, 2023)
View of Volume 66, Special Issue, September 2021 In January 2020, the Council of Europe has rejected a resolution that recommends reasonable accommodation of employee’s religious practices in the workplace. The concept of reasonable accommodation emerged in the United States and in Canada to allow some flexibility in the application of laws to achieve substantial equality for all, as uniform application of seemingly neutral laws can cause disadvantages to ethnic or religious minorities, and people with disability. However, reasonable accommodation of religious practices in the workplace such as hospitals is often criticised in two ways; first, it makes it easier for the doctors to register a conscientious objection against providing abortion or reproductive treatment and thus harms women’s reproductive rights. Second, in the same manner, medical professionals may use reasonable accommodation as an excuse to refrain from providing certain medical care to sexual minorities. The purpose of this paper is to indicate that such secularist criticisms of reasonable accommodation are implausible. To show this, this paper first reviews the idea of reasonable accommodation in North America and Europe. Then, the reasonable accommodation debate occurred in Québec, Canada and the report by Bouchard-Taylor Commission (2007-2008) are examined in light of theories of deliberative democracy to illustrate the asymmetry of power between the majority and the minority groups in the negotiation process. Lastly, this paper argues that reasonable accommodation as a means to negotiate the demands for accommodation of religious practices is limited. Thus it is unlikely to undermine the fundamental liberal values of the majority.